2019
DOI: 10.1111/apha.13357
|View full text |Cite
|
Sign up to set email alerts
|

Distant organ dysfunction in acute kidney injury

Abstract: Acute kidney injury (AKI) is a common complication in critically ill patients and it is associated with increased morbidity and mortality. Epidemiological and clinical data show that AKI is linked to a wide range of distant organ injuries, with the lungs, heart, liver, and intestines representing the most clinically relevant affected organs. This distant organ injury during AKI predisposes patients to progression to multiple organ dysfunction syndrome and ultimately, death. The strongest direct evidence of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 100 publications
1
22
0
1
Order By: Relevance
“…Protein expression levels were determined via western blot as previously described [45]. After cell collection, protein lysis and extraction were performed using RIPA lysis buffer (R0278, Sigma-Aldrich, USA), and the concentration of extracted protein was measured using the Bicinchoninic acid (BCA) protein assay kit (AR0146, Boster Bio, Pleasanton, CA, USA) [46]. Then, 20 μg protein lysates samples were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE; P0012AC, Beyotime, China) and transferred onto polyvinylidene fluoride (PVDF) membranes (FFP36, Beyotime, China), which were blocked with fat-free milk (5%) for 2 hours and incubated with primary antibodies at 4°C overnight; β-actin was used as internal control [47,48].…”
Section: Mitochondrial Membrane Potential (Mmp) Assessmentmentioning
confidence: 99%
“…Protein expression levels were determined via western blot as previously described [45]. After cell collection, protein lysis and extraction were performed using RIPA lysis buffer (R0278, Sigma-Aldrich, USA), and the concentration of extracted protein was measured using the Bicinchoninic acid (BCA) protein assay kit (AR0146, Boster Bio, Pleasanton, CA, USA) [46]. Then, 20 μg protein lysates samples were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE; P0012AC, Beyotime, China) and transferred onto polyvinylidene fluoride (PVDF) membranes (FFP36, Beyotime, China), which were blocked with fat-free milk (5%) for 2 hours and incubated with primary antibodies at 4°C overnight; β-actin was used as internal control [47,48].…”
Section: Mitochondrial Membrane Potential (Mmp) Assessmentmentioning
confidence: 99%
“…It was reported that 5% of the confirmed cases was in need of intensive care during the COVID-19 outbreak [21]. Renal impairment was found in 63% of the COVID-19 cases in one ongoing case study [22], which may contribute to multiple organ failure and death [23]. As the situation of the current pandemic evolves, extracorporeal organ support readiness has become a crucial part of care delivery [24].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The mitochondrial NTT-MMP-2 isoform was also evaluated in acute kidney injury , a frequent complication in severely ill patients that may progress to chronic kidney disease . Mitochondria dysfunction increases oxidative stress and cause tubular inflammation, one of the major fibrotic processes in renal diseases ( Maekawa and Inagi, 2019 ; Husain-Syed et al, 2020 ). Wild-type mice and transgenic NTT-MMP-2 mice were submitted to 40 min of unilateral renal IRI, and the contralateral non-clamped kidney was evaluated for systemic inflammatory responses ( Ceron et al, 2017 ).…”
Section: Ntt-mmp-2 and Renal Dysfunction And Kidney Diseasesmentioning
confidence: 99%